KONSEP TASAWUF DALAM ISLAM DENGAN METODE PENDEKATAN MURAQABAH - Mila Vedira; Amelia; Yarhami Fadillah; Nunu Burhanuddin (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
The teachings of Sufism in Islam are not only a discussion about a person's approach to God, but are part of the Islamic scientific treasury in general. As is already known, Sufism is a method or way to get closer to the Khaliq. namely by applying the concepts contained in the teachings of Sufism. The methods in Sufism direct humans to be as close as possible to Allah Ta'ala. The existence of the characteristic of muroqobah in humans can encourage a person to carry out activities with full awareness, he knows what he is doing and he knows what consequences will occur if he does it, so that he carries out activities not haphazardly and carefully, every activity he has thought about beforehand. When viewed in the context of morals, what is meant by muroqobah is a good and commendable mental attitude by feeling that he is always under Allah's surveillance and attention or is said to be under Allah's supervision because Allah is always with him wherever and whenever.